Proceedings of the Vertical Flight Society 77th Annual Forum 2021
DOI: 10.4050/f-0077-2021-16697
|View full text |Cite
|
Sign up to set email alerts
|

Axial Descent of Variable-Pitch Multirotor Configurations: An Experimental and Computational Study for Mars Deployment Applications

Abstract: For future helicopter-only Mars missions, NASA-JPL has proposed a novel entry, descent, and landing technique, in which the rotorcraft is deployed from the aeroshell in mid-air before landing. However, this approach is likely to subject the rotorcraft to unfavorable vortex ring state aerodynamics during deployment. To address this, the performance of a variable-pitch multirotor in axial descent was investigated using two parallel approaches: an experimental free-flight wind tunnel campaign and analogous comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…rotor pair and it can be shown here that a greater geometric pitch, 𝜃 .75 (compare with table 1) reduces variation of the mean thrust with descent rate. This is consistent with previous studies of large-scale (Brown, Leishman, Newman, & Perry, 2002) and small-scale rotors (Langkamp & Crowther, 2010;Shetty & Selig, 2011;Veismann et al, 2021). Another noteworthy observation from figure 6 is that the critical descent rate ratio appears to remain largely unchanged at approximately −1.2 > v c /v h > −1.3 for all test runs and rotor sizes, confirming that v c /v h is the primary scaling for VRS aerodynamics.…”
Section: Discussion Of Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…rotor pair and it can be shown here that a greater geometric pitch, 𝜃 .75 (compare with table 1) reduces variation of the mean thrust with descent rate. This is consistent with previous studies of large-scale (Brown, Leishman, Newman, & Perry, 2002) and small-scale rotors (Langkamp & Crowther, 2010;Shetty & Selig, 2011;Veismann et al, 2021). Another noteworthy observation from figure 6 is that the critical descent rate ratio appears to remain largely unchanged at approximately −1.2 > v c /v h > −1.3 for all test runs and rotor sizes, confirming that v c /v h is the primary scaling for VRS aerodynamics.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The obtained flow fields of this study can be compared with computational flow field results of closely arranged twin-rotor (Takii et al, 2020) and multirotor (McQuaid et al, 2020;Veismann et al, 2021) configurations in axial descent found in the literature. In the interest of brevity, this comparison will be qualitative in nature and readers are encouraged to consult the provided literature for their own, in-depth analysis.…”
Section: Flow Field Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…3 Additionally, a strong lowfrequency oscillatory behavior of the airloads is generally observed, 4,5 leading to severe vibrations that can ultimately manifest themselves in large vehicle attitude oscillations. 6 This performance degradation and the increased vibrational loads in axial descent can considerably limit the controllability and operational margins of multirotor platforms.…”
Section: Introductionmentioning
confidence: 99%
“…New studies delving further into the analysis of these vehicles range topics covering comprehensive and CFD analyses, handling qualities, system design, hazard analysis, and wind-tunnel testing [36][37][38][39][40][41][42][43][44][45][46][47]. Of particular interest to this work are recent studies of mid-air deployment and high rates of descent with these vehicles [48][49][50][51][52]. Some works have also looked at improving the design approach specifically for coaxial and octocopter configurations [53,54].…”
Section: Introductionmentioning
confidence: 99%